1974
DOI: 10.1111/j.1432-1033.1974.tb03593.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Basic Amino‐Acid Residues

Abstract: The interaction of four basic polyamino acids, poly(L-lysine), poly(L-ornithine), poly(L-arginine) and poly(L-homoarginine) with nucleotides was investigated using equilibrium dialysis and circular dichroism. Polyhomoarginine was prepared by guanidization of polylysine. The interaction of 5'-GMP exhibited equal values for the binding cooperativity in all cases, indicating that nucleotidenucleotide interaction, i.e. the stacking tendency of the guanine base, was the origin of this affinity. The affinity paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Also, thermodynamic and kinetic analyses of biomolecular interactions reveal details of the energetic and dynamic features of molecular recognition processes, and complement structural analyses of the free and complexed conformations. One of the first studies involving determination of thermodynamic parameters of nucleotides and some amino acids was published in 1974 (Wagner and Arfmann, 1974). The equilibrium constants determined in this study by equilibrium dialysis and circular dichroism shows that Arg have the stronger affinities in the order:…”
Section: Comparison Of Interactions Databases Of Protein-dna Interfacesmentioning
confidence: 65%
“…Also, thermodynamic and kinetic analyses of biomolecular interactions reveal details of the energetic and dynamic features of molecular recognition processes, and complement structural analyses of the free and complexed conformations. One of the first studies involving determination of thermodynamic parameters of nucleotides and some amino acids was published in 1974 (Wagner and Arfmann, 1974). The equilibrium constants determined in this study by equilibrium dialysis and circular dichroism shows that Arg have the stronger affinities in the order:…”
Section: Comparison Of Interactions Databases Of Protein-dna Interfacesmentioning
confidence: 65%
“…have evaluated chromatographically the interaction propensities of amino acids and different pyridine derivatives in water . Finally, several groups have studied interactions between different nucleotides and polyamino acids, focusing typically on polylysine or polyarginine peptides . The scarcity of the experimental studies in this context can in part be attributed to the low solubility of bases and some side chains as well as the weak interaction strengths involved.…”
Section: Nucleobase/amino Acid Affinities As a Basis For Understandinmentioning
confidence: 99%
“…That nucleotides bind to amino acids has been clearly shown. For example, Wagner & Arfmann (1974) have demonstrated that large numbers of nucleotide molecules bind to poly(amino acids) such as polylysine and polyarginine. Since RNAase contains four arginine and ten lysine residues, all in positions well exposed to aqueous solvents (Richards & Wyckoff, 1971), weak binding sites may exist on RNAase for a large number of nucleotides, particularly since models based on the X-ray-diffraction data of Wyckoff et al (1967) for RNAase S show that 11 of these residues occur in a cluster centred around lysine-31.…”
Section: V61 153mentioning
confidence: 99%